Indonesian Football Supporters' Fanaticism: A Collective Behavior Perspective - Alessandro Inouva Collin; Heny Setyawati (Jurnal Master Penjas & Olahraga, 2026)
Football is a highly popular sport in Indonesia, where supporters often develop strong emotional attachments that shape fanaticism as a social and cultural identity. This study aims to analyze the formation of fanaticism among B6 Surakartans supporters of Persis Solo. A qualitative descriptive approach was used, with six participants selected through purposive sampling, including members, administrators, and supporters. Data were collected through interviews and validated using source triangulation. The analysis involved data reduction, presentation, and conclusion drawing. The findings show that shared emotions, common interests, and collective experiences influence supporter fanaticism. The atmosphere in the stands strengthens emotional bonds and togetherness, while informal norms guide supporter behavior. Fanaticism also reinforces group identity and is shaped by rivalry with other supporters. It can be concluded that supporter fanaticism is formed through social interactions and shared values, which can promote solidarity but also carry the risk of conflict if not properly managed.